Protocol for a Phase 1, Open-Label, Multiple-Center, Dose-Escalation Study to Evaluate the Safety and Tolerability of ADR-001 in the Treatment of Immunoglobulin A Nephropathy - Tanaka, Akihito; Furuhashi, Kazuhiro; Fujieda, Kumiko; Maeda, Kayaho; Saito, Shoji; Mimura, Tetsushi; Saka, Yosuke; Naruse, Tomohiko; Ishimoto, Takuji; Kosugi, Tomoki; Kinoshita, Fumie; Kuwatsuka, Yachiyo; et al. (Frontiers in Medicine, 2022)
Introduction: Immunoglobulin A (IgA) nephropathy is a disease that presents with urinary symptoms such as glomerular hematuria and urinary protein positivity, with predominant deposition of IgA in the mesangial region of the glomerulus. Corticosteroids are mainly used for treatment; however, infection is a serious adverse event, and evidence regarding therapeutic efficacy is insufficient, thus new treatments are strongly desired. Mesenchymal stem cells (MSCs) contribute to the amelioration of inflammation and recovery of organ function in inflammatory environments by converting the character of leukocytes from inflammatory to anti-inflammatory and inducing the proliferation and differentiation of organ component cells, respectively. These properties of MSCs have led to their clinical application in various inflammatory diseases, but this study is the first clinical trial of MSCs for refractory glomerulonephritis in the world. This study is registered and assigned the number, jRCT2043200002 and NCT04342325. Methods: This will be a phase 1, open-label, multiple-center, dose-escalation study of adult patients with refractory IgA nephropathy resistant to or difficult to treat with existing therapies. ADR-001 will be administered intravenously to from three to six patients at a dose of 1× 108 cells once in the first cohort and to six patients twice at two-week intervals in the second cohort, and observation will continue until 52 weeks. The primary endpoint will be the evaluation of adverse events up to 6 weeks after the start of ADR-001 administration. Secondary endpoints will be the respective percentages of patients with adverse events, clinical remission, partial remission, remission of urine protein, remission of hematuria, time to remission, changes in urine protein, hematuria, and estimated glomerular filtration rate. Results: Following the administration of ADR-001 to patients with IgA nephropathy, the respective percentages of patients with adverse events, asymptomatic pulmonary emboli, clinical remission, partial remission, urine protein remission, hematuria remission, their time to remission, changes in urine protein, hematuria, and glomerular filtration rate will be determined. Conclusion: This study will evaluate the safety and tolerability of ADR-001 and confirm its therapeutic efficacy in adult patients with refractory IgA nephropathy.